Effect of Spun Velocities and Composition on the R‒phase and Thermomechanical Behavior in Ti‒Ni Ribbons Electrically Heated - Cuéllar, Enrique López; Mendoza, Esaú Nuñez; Araújo, Carlos José de; Walle López, Beatriz Cristina; Otubo, Jorge; González, Cezar Henrique (2016)
This work deals with structural, electrical and mechanical characterization of Ti‒50.13Ni and Ti‒49.62Ni (at.%) shape memory alloys (SMAs) fabricated at different circumferential wheel velocities. The effect of wheel velocity, chemical composition and heat treatments are investigated. The characterization of crystallographic phases of the Ti‒Ni ribbons was carried out using X-ray diffraction. Electrical resistance variations as function of temperature (∆R/R %) were analyzed using a non-commercial technique, which consists in a thermal-adjustable bath apparatus revealing the temperatures of B2→R→B19´ two stage transformation, whereby the presence of R‒phase can be definitively confirmed. The Stress-Assisted Two-Way Memory Effect was measured by an own designed apparatus with an Linear Variable Differential Transformer captor and a current controlled heating, and results indicate that the as-spun condition, promotes the Stress-Assisted Two-Way Memory Effect. On the other hand, increments in Ni content tend to decrease transformation temperatures and high wheel velocities help to the R‒phase formation.